Synthesis and Characterization of Some Trivalent and Tetravalent Derivatives of 2- Hydroxy-1-naphthoic Acid - Deepti Joshi; T. K. Joshi (E-Journal of Chemistry)
The trivalent derivatives (B, Al, As, Sb & Fe) and tetravalent derivatives (Si, Ti & Se) of 2-hydroxy-1-naphthoic acid have been prepared by the interaction of their corresponding isopropoxide with letter in different molar ratio viz. 1:3 &1:4 in benzene medium. The prepared compounds generally obtained as coloured solids and amongst them those containing isopropoxy groups were found to be hygroscopic. All these compound were characterized by azeotrope and elemental analysis as well as by IR, PMR and mass spectral measurements. These spectral data have facilitated in elucidating the mode of bonding of the said metals and non-metals in these compounds with 2-hydroxy-1-naphthoic acid.